Vídeo ao vivo no Teat(r)o Oficina: intermidialidade em Cacilda!!!! - fábrica de cinema e teatro - Vinagre, Ivan Augusto Soares (Universidade Federal de São Carlos, 2020)
In this dissertation, according to theories of the field of intermediality, I propose an exploration of the play "Cacilda!!!! - cinema and theater factory", staged by Teat(r)o Oficina in 2013. I want to demonstrate how live video production practices have been perfected by the group over its 60 years of activity, as well as it's implications over the casting, music and stage direction involved in the play.
Teat(r)o Oficina: live video and intermedia in Cacilda!!!! - stage and screen factory
Keywords: Intermidialidade; Teatro; Vídeo; Intermediality; Theater; LINGUISTICA, LETRAS E ARTES::ARTES::ARTES DO VIDEO; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA; LINGUISTICA, LETRAS E ARTES::ARTES::FUNDAMENTOS E CRITICA DAS ARTES; LINGUISTICA, LETRAS E ARTES::ARTES::TEATRO